USE OF THE SYNACTHEN TEST FOR CONFIRMING SUSPECTED ADRENAL INSUFFICIENCY IN CHILDREN (Herald of the National Children's Medical Center, 2025)
To assess the effectiveness of the Synacthen test in diagnosing secondary, tertiary or iatrogenic adrenal insufficiency, as well as non-classic congenital adrenal hyperplasia (NCCAH).
Keywords: synacthen test; adrenal insufficiency; congenital adrenal hyperplasia; hypopituitarism; glucocorticoids